ARTIFICIAL INTELLIGENCE PEDAGOGICAL APPROACH FOR FOSTERING CONCEPTUAL UNDERSTANDING IN COLLEGE MATHEMATICS - Sadiqah Abdullah Al Marzooq (PUPIL: International Journal of Teaching, Education and Learning, 2026)
In this paper, we studied the implications of Artificial Intelligence (AI) in mathematics courses at the college level, with a concentration on its impact on students’ conceptual understanding. AI offers a wide range of innovative tools and adaptive platforms that enable instructors to explain math concepts in inventive and engaging ways. Our study examines how these tools can improve students’ understanding, as these platforms facilitate individualized learning experiences, represent concepts in various ways, and offer immediate feedback. Our goal is to evaluate the success of AI-driven techniques in supporting different learning methodologies and improving student engagement in the mathematical classroom. The findings shall assist us in recognizing the power of AI in transferring teaching approaches in college education to enhance conceptual learning.